Arabidopsis FAB1/PIKfyve Proteins Are Essential for Development of Viable Pollen - Whitley, Paul (American Society of Plant Biologists, 2009)
Phosphatidylinositol 3,5-bisphosphate [PtdIns(3,5)P(2)] is a phospholipid that has a role in controlling membrane trafficking events in yeast and animal cells. The function of this lipid in plants is unknown, although its synthesis has been shown to be up-regulated upon osmotic stress in plant cells. PtdIns(3,5)P(2) is synthesized by the PIKfyve/Fab1 family of proteins, with two orthologs, FAB1A and FAB1B, being present in Arabidopsis (Arabidopsis thaliana). In this study, we attempt to address the role of this lipid by analyzing the phenotypes of plants mutated in FAB1A and FAB1B. It was not possible to generate plants homozygous for mutations in both genes, although single mutants were isolated. Both homozygous single mutant plant lines exhibited a leaf curl phenotype that was more marked in FAB1B mutants. Genetic transmission analysis revealed that failure to generate double mutant lines was entirely due to inviability of pollen carrying mutant alleles of both FAB1A and FAB1B. This pollen displayed severe defects in vacuolar reorganization following the first mitotic division of development. The presence of abnormally large vacuoles in pollen at the tricellular stage resulted in the collapse of the majority of grains carrying both mutant alleles. This demonstrates a crucial role for PtdIns(3,5)P(2) in modulating the dynamics of vacuolar rearrangement essential for successful pollen development. Taken together, our results are consistent with PtdIns(3,5)P(2) production being central to cellular responses to changes in osmotic conditions.